Gene Expression Profiles Stratified according to Type 1 Diabetes Mellitus Susceptibility Regions - Rassi, Diane Meyre; Junta, Cristina Moraes; Fachin, Ana Lucia; Sandrin-Garcia, Paula; Mello, Stephano; Silva, Guilherme Liberato; Evangelista, Adriane Feijo; Magalhaes, Danielle Aparecida; Wastowski, Isabela Jube; Crispim, Janaina Oliveira; Martelli-Palomino, Gustavo; Mores Fernandes, Ana Paula; et al. (Blackwell Publishing, 2008)
The MHC region (6p21) aggregates the major genes that contribute to susceptibility to type 1 diabetes (T1D). Three additional relevant susceptibility regions mapped on chromosomes 1p13 (PTPN22), 2q33 (CTLA-4), and 11p15 (insulin) have also been described by linkage studies. To evaluate the contribution of these susceptibility regions and the chromosomes that house these regions, we performed a large-scale differential gene expression on lymphomononuclear cells of recently diagnosed T1D patients, pinpointing relevant modulated genes clustered in these regions and their respective chromosomes. A total of 4608 cDNAs from the IMAGE library were spotted onto glass slides using robotic technology. Statistical analysis was carried out using the SAM program, and data regarding gene location and biological function were obtained at the SOURCE, NCBI, and FATIGO programs. Three induced genes were observed spanning around the MHC region (6p21-6p23), and seven modulated genes (5 repressed and 2 repressed) were seen spanning around the 6q21-24 region. Additional modulated genes were observed in and around the 1p13, 2q33, and 11p15 regions. Overall, modulated genes in these regions were primarily associated with cellular metabolism, transcription factors and signaling transduction. The differential gene expression characterization may identify new genes potentially involved with diabetes pathogenesis.
Keywords: type 1 diabetes; susceptibility regions; HLA; gene expression profile